NAHDLATUL ULAMA CONFLICT DUE TO THE 1991 SOCIAL PHILANTHROPIST DONATION (SDSB) : Konflik Nahdlatul Ulama karena Sumbangan Dermawan Sosial Berhadiah (SDSB) 1991 - Teddiansyah Nata Negara; Samsudin Samsudin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study examines the internal conflict within Nahdlatul Ulama (NU) triggered by the organization’s involvement in a funding request to the Ministry of Social Affairs through the Social Welfare Service Charity Foundation (YDBKS), which managed the Social Philanthropy with Prizes (SDSB) program a scheme widely associated with gambling. Although the funds were intended for the renovation of the Hasyimiyah Foundation in Tuban, the issue escalated into a major controversy because it contradicted NU’s official stance on SDSB. Previous studies have discussed NU’s institutional politics, yet the specific dilemma arising from its entanglement with state-linked fundraising mechanisms has not been sufficiently analyzed. Therefore, this research aims to clarify how the NU dan SDSB case reflects tensions between pragmatic institutional needs and normative religious principles. Using the historical method consisting of heuristics, source criticism, interpretation, and historiography, the study reveals that the conflict was not merely administrative but exposed deeper moral inconsistencies, internal leadership fragmentation, and contested legitimacy within NU. The findings demonstrate the urgency of ethical coherence and transparent governance in religious organizations facing socio-political pressures. The study contributes novelty by framing the NU–SDSB controversy as a critical lens for understanding the negotiation between moral authority and pragmatic decision-making in modern Islamic institutions.